PERBANDINGAN PENGARUH INDEKS PRESTASI KUMULATIF (IPK), LITERASI KEUANGAN, DAN PENJURUSAN TERHADAP SPENDING HABITS MAHASISWA - Fransiska Octaviani Tianika; Rosemarie Sutjiati Njotoprajitno (FAKULTAS EKONOMI UNIVERSITAS FLORES, 2021)
Financial literacy is indicated to be able to help personal finances such as in the case of money circulation which will further control one's spending habit. lack of financial literacy causes failure in terms of managing finances. This research is in the field of personal financial planning/management which aims to to examine the comparison of the effects of GPA, financial literacy, and study programs on spending habits. This research uses collection of primary data obtained from students from the Faculty of Economics and Informatics of the Christian University of Marantha, the sample method used to collect sample is purposive sampling. The final results of the research showed that partially, GPA had no effect on spending habits, financial literacy had no effect on spending habits, and majors had no effect on spending habits. Simultaneously, GPA, financial literacy and majors had significant effect on spending habits. This result shows student academic achievement and financial literacy need to complement each other in order to influence student spending habits.